Cardiovascular health education intervention in the Prison of Soria - M.M. Martínez-Delgado; C. Ramírez-López (Sociedad Española de Sanidad Penitenciaria, 2016)
Objective: To promote awareness of healthy lifestyles, to help decrease the risk factors that cause cardiovascular disease, obesity, diabetes, hypertension and hyperlipidemia, through Health Education (HE). Material and Methods: Between November and December 2014 in the prison of Soria, HE intervention in cardiovascular diseases was performed. Participation was offered to 160 inmates at the Prison. The intervention consisted of individual interviews with anthropometric assessment and review of medical records and three group sessions with theoretical and practical content of these diseases, as well as dietary recommendations, Mediterranean diet and exercise. Knowledge gained from surveys conducted for that purpose was evaluated. Results: A total of 33 (21%) of 160. Average age 38.2 (35.2 to 41.3). Prevalence: Normal weight (BMI 18 to 24.9) 18 (54.5%), overweight BMI (25.0 to 29.9) 11 (33.3%), obesity (IBMI from 30) 4 (12. 1%). Cardiovascular risk (CVR) as ICC (waist hip ratio) 10 (30%) high risk, REGICOR 4 (12.1%) moderate risk. Relative risk of comorbidity in 2 (6.0%) had a slightly increased risk, 4 (12.1%) had increased risk. Conclusions: HE interventions are necessary and effective in modifying lifestyles. The calculation of CVT should serve to implement preventive measures to reduce the factors of cardiovascular risk.